Effectiveness of Nanoemulsion Formulated with Citronella and Garlic Essential Oils against Fall Armyworm (Spodoptera frugiperda) on Maize Plants - Ragil Indah Kusumawati Supernong; Ni Siluh Putu Nuryanti; Anung Wahyudi; Ratna Dewi (Biology, Medicine, & Natural Product Chemistry, 2026)
Fall armyworm (Spodoptera frugiperda J.E Smith) is a major invasive pest that threatens maize production in Indonesia. This study aimed to evaluate the activity of nanoemulsions of citronella and garlic essential oils, both individually and in combinations at ratios of 1:1, 2:1, and 1:2, against third-instar larvae of S. frugiperda. The essential oils were obtained by steam distillation and formulated into nanoemulsions using Tween 80. Toxicity was assessed via contact assays and analyzed with POLO-PC software to determine LC50 and LC95 values. The citronella–garlic ratio of 2:1 was the most promising, yielding the lowest LC50 (0.1 % at 96 hours) and consistently exhibiting strong synergistic effects at the LC50 level compared with the 1:1 and 1:2 ratios, which more frequently showed additive or antagonistic interactions. The citronella nanoemulsion displayed the smallest particle size (97.8 nm) but the highest polydispersity index (PI) (0.406), indicating lower physical stability. In contrast, the garlic nanoemulsion exhibited a particle size of 185.9 nm with a PI of 0.270, reflecting a more stable system. The citronella–garlic combination at a 2:1 ratio produced the largest particle size (204.9 nm) but the lowest PI (0.239), suggesting superior stability and a more uniform particle distribution. These findings support the potential of nanoemulsified essential oils as eco-friendly botanical insecticides.